Soft X-ray study on electronic structure of passive oxide layer of carbon steel and low alloy steel in flow-accelerated corrosion environments of pressurized water reactors. (October 2019) - Kim, Seunghyun; Kim, Taeho; Lee, Yunju; Kim, Ji Hyun
Highlights: The microstructure and chemistry of CS and LAS is investigated via STXM. A mixture of Fe 2+ and Fe 3+ was observable for CS mainly Fe3 O4 . P22 has two oxide layers composed of multiple iron oxides and chromium oxide. Mo was not observable in the passive layer of P22. Cr plays a critical role during FAC process. Abstract: Due to susceptibility of carbon steels under flow-accelerated corrosion environments, 2.25Cr-1Mo has been adopted as replacement. However, the mechanism of enhancement in the passivity has not been completely elucidated. We employed synchrotron scanning transmission X-ray microscopy to test the microstructure and chemistry of the alloys after flow-accelerated corrosion tests at 150 °C. Carbon steel exhibited a mixture of Fe 2+ and Fe 3+ states as a passive layer while 2.25Cr-1Mo presented two oxide layers composed of Fe2 O3, Fe3 O4, and FeO. A small quantity of Cr2 O3 was observed which was not enriched. Furthermore, Mo was not observed in the oxide layer of 2.25Cr-1Mo.